Impact of glycolysis enzymes and metabolites in regulating DNA damage repair in tumorigenesis and therapy - Fengyao Sun; Wen Li; Ruihang Du; Mingchan Liu; Yi Cheng; Jianxing Ma; Siyuan Yan (Cell Communication and Signaling)
Abstract Initially, it was believed that glycolysis and DNA damage repair (DDR) were two distinct biological processes that independently regulate tumor progression. The former metabolic reprogramming rapidly generates energy and generous intermediate metabolites, supporting the synthetic metabolism and proliferation of tumor cells. While the DDR plays a pivotal role in preserving genomic stability, thus resisting cellular senescence and cell death under both physiological and radio-chemotherapy conditions. Recently, an increasing number of studies have shown closely correlation between these two biological processes, and then promoting tumor progression. For instance, lactic acid, the product of glycolysis, maintains an acidic tumor microenvironment that not only fosters cell proliferation and invasion but also facilitates DDR by enhancing AKT activity. Here, we provide a comprehensive overview of the enzymes and metabolites involved in glycolysis, along with the primary methods for DDR. Meanwhile, this review explores existing knowledge of glycolysis enzymes and metabolites in regulating DDR. Moreover, considering the significant roles of glycolysis and DDR in tumor development and radio-chemotherapy resistance, the present review discusses effective direct or indirect therapeutic strategies targeted to glycolysis and DDR.